Transgenerational Effects of Parental Diet on Offspring Development and Disease Resistance in Flies - Dinh, Hue; Nguyen, Binh; Morimoto, Juliano; Lundback, Ida; Kumar, Sheemal S.; Ponton, Fleur (Frontiers in Ecology and Evolution, 2021)
The environmental conditions experienced by parents influence next generations, with the parental nutritional status playing an important role in shaping offspring phenotypes. Our understanding of transgenerational effects of parental diet on offspring pathogen resistance is, however, poorly documented. We manipulated the quality of parental diet (i.e., mother, father, or both) and measured effects on offspring development and survival after an immune challenge by septic infection. We used Bactrocera tryoni as host model infected with the pathogenic bacterium, Serratia marcescens. Our results showed no significant effect of maternal, or paternal, diet on offspring resistance. Interestingly, when the diet of both parents was manipulated, sons from parents fed either carbohydrate- or protein-biased diets had higher survival upon pathogen infection than sons from parents fed balanced diets. The quality of the parental diet had no effect on offspring developmental traits with the exception of egg hatching percentage which decreased when mothers were fed a protein-biased diet. Our results emphasised the complexity of nutritional transgenerational effects on offspring pathogen resistance and development.